Does a multiple myeloma polygenic risk score predict overall survival of patients with myeloma? - Macauda, Angelica; Clay-Gilmour, Alyssa; Hielscher, Thomas; Hildebrandt, Michelle A.T.; Kruszewski, Marcin; Orlowski, Robert Z.; Kumar, Shaji K.; Ziv, Elad; Orciuolo, Enrico; Brown, Elizabeth E.; Försti, Asta; Waller, Rosalie G.; et al. (Cancer epidemiology, biomarkers & prevention, 2022)
Genome-wide association studies (GWAS) of multiple myeloma in populations of European ancestry (EA) identified and confirmed 24 susceptibility loci. For other cancers (e.g., colorectum and melanoma), risk loci have also been associated with patient survival.We explored the possible association of all the known risk variants and their polygenic risk score (PRS) with multiple myeloma overall survival (OS) in multiple populations of EA [the International Multiple Myeloma rESEarch (IMMEnSE) consortium, the International Lymphoma Epidemiology consortium, CoMMpass, and the German GWAS] for a total of 3,748 multiple myeloma cases. Cox proportional hazards regression was used to assess the association between each risk SNP with OS under the allelic and codominant models of inheritance. All analyses were adjusted for age, sex, country of origin (for IMMEnSE) or principal components (for the others) and disease stage (ISS). SNP associations were meta-analyzed.SNP associations were meta-analyzed. From the meta-analysis, two multiple myeloma risk SNPs were associated with OS (P < 0.05), specifically POT1-AS1-rs2170352 [HR = 1.37; 95% confidence interval (CI) = 1.09-1.73; P = 0.007] and TNFRSF13B-rs4273077 (HR = 1.19; 95% CI = 1.01-1.41; P = 0.04). The association between the combined 24 SNP MM-PRS and OS, however, was not significant.Overall, our results did not support an association between the majority of multiple myeloma risk SNPs and OS.This is the first study to investigate the association between multiple myeloma PRS and OS in multiple myeloma.